"Diseño de un sistema de ventilación en el área de ensacado para una fabrica de balanceado" - Pérez Oñate, Álvaro Javier (2020)
The various activities carried out by workers in an industry, accompanied by the architecture, machinery and equipment of the place where these activities are carried out are the variables that generate an increase in temperature, therefore an increase in heat throughout the premises. The present research work aims to design a ventilation system in the bagging area of a balanced factory where the aforementioned variables are present, for this reason mechanical ventilation has been chosen as the best option. To design the ventilation system in the balancing plant, it was necessary to calculate the total thermal load of the premises; therefore, a detailed analysis of the different heat gains had to be performed, such as: solar thermal gain by walls and roof, thermal gain by occupants, thermal gain by lighting. It should be noted that to carry out these calculations the Carrier Manual and the ASHRAE standards were used as a reference to obtain the amount of cfm (cubic feet per minute), which are needed in the area to be ventilated. Once the necessary amount of ventilation was obtained, the different ventilation equipment were selected and placed inside the balancing factory, such as: fan, ducts, filters and louvers. To determine the optimal working conditions of the workers, Reglamento de Seguridad y Salud de los Trabajadores y Mejoramiento del Medio Ambiente de Trabajo (Decreto ejecutivo 2393). In order to determine the cost of the ventilation system, an economic analysis was carried out based on equipment and labor costs. Keywords: Ventilation, temperature, confort, heat.